Students’ perceptions of the quality of podcasts and vodcasts in teaching academic writing skills at a distance education institution - Mohale, Ntshimane Elphas (Acitya: Journal of Teaching and Education, 2025)
First-year students in an open distance e-learning institution face academic writing challenges. These challenges can lead to higher dropout rates, increased failures, and delayed completion of qualifications. Key challenges include poor adherence to academic writing conventions, generating suitable content, citation and referencing issues, and writing style deficiencies. To address these academic writing challenges, podcasts and vodcasts were introduced as supplemental support tools. Podcasts and vodcasts aimed to reduce transactional distance and increase collaborative teaching and learning interactions. The student body, consisting of 30,000 individuals from diverse socio-economic and cultural backgrounds, participated in the study. A qualitative research approach was employed, collecting data through online evaluation questions and focus group discussions. The findings revealed that students faced numerous issues: poor sound quality due to weak voice projection, lecturers speaking too quickly and using complex language, excessively lengthy multimedia files, and information overload, which hindered comprehension. Based on students’ responses, guidelines were developed to assist and inform current and future lecturers about creating high-quality podcasts and vodcasts. These guidelines aim to enhance the academic writing skills of first-year students and create a community of practice among lecturers. Recommendations include maintaining a calm, audible, and neutral tone of voice, limiting podcasts and vodcasts to 15 minutes, communicating in straightforward plain English, simplifying module content, and providing transcriptions. These measures are intended to make multimedia resources more effective and accessible, thereby improving students’ academic performance and retention.